CD8 Knockout Mice Are Protected from Challenge by Vaccination with WR201, a Live Attenuated Mutant of Brucella melitensis - Samuel L. Yingst; Mina Izadjoo; David L. Hoover (Clinical and Developmental Immunology)
CD8+ T cells have been reported to play an important role in defense against B. abortus infection in mouse models. In the present report, we use CD8 knockout mice to further elucidate the role of these cells in protection from B. melitensis infection. Mice were immunized orally by administration of B. melitensis WR201, a purine auxotrophic attenuated vaccine strain, then challenged intranasally with B. melitensis 16M. In some experiments, persistence of WR201 in the spleens of CD8 knockout mice was slightly longer than that in the spleens of normal mice. However, development of anti-LPS serum antibody, antigen-induced production of γ-interferon (IFN-γ) by immune splenic lymphocytes, protection against intranasal challenge, and recovery of nonimmunized animals from intranasal challenge were similar between normal and knockout animals. Further, primary Brucella infection was not exacerbated in perforin knockout and Fas-deficient mice and these animals’ anti-Brucella immune responses were indistinguishable from those of normal mice. These results indicate that CD8+ T cells do not play an essential role as either cytotoxic cells or IFN-γ producers, yet they do participate in a specific immune response to immunization and challenge in this murine model of B. melitensis infection.